1987
DOI: 10.1103/physrevb.35.6560
|View full text |Cite
|
Sign up to set email alerts
|

Damage processes and magnetic field orientation in ferrimagnetic oxidesY3Fe5

Abstract: Mossbauer spectroscopy of damage induced by energetic Ar, Kr, and Xe ions in the giga-electronvolt range in two ferrimagnetic oxides, Y3Fe5012 and BaFe120l9, is presented. The enhancement of the paramagnetic phase observed after an irradiation with high-energy deposition (Xe and Kr ions) compared to low-energy deposition (Ar ions) supports a damage mechanism based on the electronic stopping power. Threshold energy-deposition values close to 17 and 25 MeVcm mg ' have thus been determined for Y3Fe50» and BaFelzO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…Above this threshold, the track size in a given material becomes larger with increasing energy loss. Close to the track formation threshold, Houpert et al 28 showed that the track morphology changes from continuous to discontinuous, consisting of less-extended damage fragments (the effect has been ascribed to fluctuating energy loss processes, 29 but it has not yet been clarified). With decreasing energy loss, the fragments become shorter, and the diameter does not change but remains constant at around 2-3 nm.…”
Section: A Tracks In Amorphizable Insulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Above this threshold, the track size in a given material becomes larger with increasing energy loss. Close to the track formation threshold, Houpert et al 28 showed that the track morphology changes from continuous to discontinuous, consisting of less-extended damage fragments (the effect has been ascribed to fluctuating energy loss processes, 29 but it has not yet been clarified). With decreasing energy loss, the fragments become shorter, and the diameter does not change but remains constant at around 2-3 nm.…”
Section: A Tracks In Amorphizable Insulatorsmentioning
confidence: 99%
“…paramagnetic transition, 29,36 or electrical resistivity changes, 37 overcome this problem by measuring the overall track damage of a given sample. In such studies typically the damage cross section (σ ) is deduced by analyzing the amount of transformed material as a function of the ion fluence [31][32][33][34][35][36][37] and applying a Poisson statistical model that takes into account sublinear effects due to track overlapping.…”
Section: -1mentioning
confidence: 99%
“…In materials like Y 3 Fe 5 O 12 , BaFe 12 O 19 and NiFe 2 O 4 , the magnetic properties are very sensitive to the irradiation-induced disorder, which results in a decrease of the saturation magnetization [1,2]. Mossbauer spectrometry experiments have verified [3] that a paramagnetic phase is induced. The damage induced in magnetic insulators by high-energy heavy ion irradiation has resulted in the formation of latent tracks.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, it is well known that every single ion generates a well-defined amorphous track of nanometre diameter whenever its stopping power is above such a threshold value. These tracks have been observed and investigated by a variety of techniques [16][17][18][19][20][21][22][23][24][25][26][27][28][29] and offer interesting possibilities for nano-structuring and nano-patterning of materials in electronics and photonics [11,[30][31][32]. Although the detailed structure of the tracks is not definitely known for most materials and it may be quite complex, it has been, indeed, observed that it includes a central amorphous core surrounded by an extensive halo containing elastically stressed regions as well as point defects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed structure of the tracks is not definitely known for most materials and it may be quite complex, it has been, indeed, observed that it includes a central amorphous core surrounded by an extensive halo containing elastically stressed regions as well as point defects (e.g. colour centres) and extended defects [10,25,26]. Understanding the defect structure of the halo requires a definite theoretical model to account for the formation of defects during electronic damage.…”
Section: Introductionmentioning
confidence: 99%